2003
DOI: 10.1590/s0006-87052003000100005
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia do herbicida glifosato-potássico submetido à chuva simulada após a aplicação

Abstract: Apesar de possuir boa ação herbicida, alguns fatores afetam a eficácia do glifosato e, nesse contexto, realizaram-se estudos buscando formulações mais eficazes. O experimento foi instalado em área do Campus da FCAV-UNESP, Jaboticabal (SP). Testou-se a formulação potássica de glifosato comparada com solução aquosa e grânulos dispersíveis em água à mesma dosagem (0,36 kg.ha-1 e.a) em cinco intervalos (1, 2, 4, 6 e > 48 horas) sem chuva após a aplicação, comparados com uma testemunha sem uso de herbicidas. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
1
3
0
2
Order By: Relevance
“…The absorption of glyphosate potassium salt formulation is slow and if there is rainfall, it may be washed and this reduces the control of % of these species. The obtained results by several researchers have shown that the absorbtion time of glyphosate in the potassium salt formulation ranges from 4 to 8 h (Bastiani et al, 2000;Jakelaitis et al, 2001;Martini et al, 2003;Werlang et al, 2003;Martins et al, 2009). During evaluation of the size of the stomata, a correlation was verified with the microscopic analysis discussed before (Figure 2) and it was observed that with the passage of time, there was a reduction in the width while the length did not experience any substantial change.…”
Section: Anatomical Studiessupporting
confidence: 54%
“…The absorption of glyphosate potassium salt formulation is slow and if there is rainfall, it may be washed and this reduces the control of % of these species. The obtained results by several researchers have shown that the absorbtion time of glyphosate in the potassium salt formulation ranges from 4 to 8 h (Bastiani et al, 2000;Jakelaitis et al, 2001;Martini et al, 2003;Werlang et al, 2003;Martins et al, 2009). During evaluation of the size of the stomata, a correlation was verified with the microscopic analysis discussed before (Figure 2) and it was observed that with the passage of time, there was a reduction in the width while the length did not experience any substantial change.…”
Section: Anatomical Studiessupporting
confidence: 54%
“…Jakelaitis et al (2003), avaliando diferentes formulações de glyphosate em condições de chuva, constatou-se que com uma hora depois da aplicação com chuva o ZQ proporcionou o melhor controle na espécie estuda, levando-nos a afirmar que sua absorção é mais rápida que de outras formulações, constituindo a uma dessecação mais rápida. O mesmo aconteceu em trabalho realizado por Martini et al (2003), na aplicação de glyphosate potássico em Brachiaria plantaginea, Brachiaria decumbens e Digitaria horizontalis, onde a incidência de chuva uma horas após a aplicação, a média de controle foi de 40% aos 14 dias após o tratamento, e atingiu 65% em 28 dias, sobressaindo em relação às demais formulações.…”
Section: Resultsunclassified
“…Já aos 8 DAD, a aveia-preta apresentou o maior controle diferindo significativamente dos demais tratamentos para os dois produtos utilizados, onde novamente os piores índices de eficiência foi com a espécie ervilhaca, para ambos os herbicidas. Segundo Martini et al (2003), os melhores resultados e controle aparecem de forma mais evidente em algumas espécies, devido a maior suscetibilidade das espécies a molécula de glyphosate.…”
Section: Resultsunclassified
“…Smith et al (2016) stated that it is important to understand which irrigation rates are most appropriate for herbicide incorporation to optimize weed management programs. The amount and intensity of the rainfall can influence the rate of absorption and translocation of the herbicides, as well as the efficiency of the weed control (Martini et al 2003;Monquero & Silva 2007). This study aimed to evaluate effects of imazethapyr placement on its phytotoxic activity against selected weeds and to determine whether the phytotoxicity of imazethapyr in combination with OPF mulches could be influenced by rainfall amount.…”
Section: Introductionmentioning
confidence: 99%